2007
DOI: 10.1021/jf071316u
|View full text |Cite
|
Sign up to set email alerts
|

HPLC–PDA–MS/MS of Anthocyanins and Carotenoids from Dovyalis and Tamarillo Fruits

Abstract: Anthocyanins and carotenoids are natural pigments responsible for the color of vegetables and fruits, and they are also bioactive compounds, both demonstrating important biological, therapeutic, and preventative properties. Considering the biodiversity of edible fruits, high performance liquid chromatography coupled to photodiode array and mass spectrometry detectors (HPLC-PDA-MS) was used to establish the composition of carotenoids and anthocyanins from dovyalis and tamarillo fruits. Ten anthocyanins and 26 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
116
3
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(158 citation statements)
references
References 31 publications
15
116
3
12
Order By: Relevance
“…Fragments at m/z 545, 489, 435, 395 and 339 were detected as characteristic for phytoene, and at m/z 543, 461, 406 and 338 for phytofluene [96,100].…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…Fragments at m/z 545, 489, 435, 395 and 339 were detected as characteristic for phytoene, and at m/z 543, 461, 406 and 338 for phytofluene [96,100].…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…Os cromatogramas foram processados a 520 nm, e os espectros, obtidos entre 250 e 600 nm. As antocianinas foram identificadas através das características dos espectros UV-visível e de massas, comparando com padrões e dados da literatura (SELLAPPAN et al, 2002;FAN-CHIANG;WU;PRIOR, 2005;ZANATTA et al, 2005;MERCADANTE, 2007a).…”
Section: Methodsunclassified
“…Os espectros UV-visível foram obtidos entre 250 e 600 nm, e os cromatogramas foram processados a 450 nm. Os carotenoides foram identificados considerando a seguinte combinação de informações: ordem de eluição, cocromatografia com padrões, característi-cas dos espectros UV-visível (l máx , estrutura fina, intensidade do pico cis) e de massas comparados com dados da literatura (BRITTON, 1995;MARINOVA;RIBAROVA, 2007;MERCADANTE, 2007a;MERCADANTE, 2007b).…”
Section: Methodsunclassified
“…The knowledge of the chemical structures and sensory properties of key taste molecules would be helpful for the development of added-value food products. Additionally, Some scientific studies related to the physicochemical composition, volatiles, pigment (carotenoids and anthocyanins), and polyphenol contents of this fruit have been published [4][5][6][7]. The volatile studies on red-variety fruits showed that the major constituents of pentane-dichloromethane liquidliquid extract were methyl hexanoate, (E)-hex-2-enal, (Z)-hex-3-en-1-ol, eugenol, and 4-allyl-2,6-dimethoxyphenol [8].…”
Section: Introductionmentioning
confidence: 99%